2005
DOI: 10.1111/j.1539-6924.2005.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate, Disaggregate, and Hybrid Analyses of Ecological Risk Perceptions

Abstract: Laypeople's perceptions of health and safety risks have been widely studied, but only a few studies have addressed perceptions of ecological hazards. We assembled a list of 39 attributes of ecological hazards from the literatures on comparative risk assessment, ecological health, environmental conservation and management, environmental psychology, and risk perception. In Study 1, 125 laypeople evaluated 83 hazards on subsets of this attribute set. Factor analysis of attribute ratings (averaged over participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 40 publications
5
40
1
Order By: Relevance
“…The above studies underscore that one's perception, in this case, risk perception is a result of complex and subjective psychological and mental processes; therefore, the study of risk perception truly requires collaboration across various disciplines. Willis et al (2005) systematically studied the methodological issues in psychometric studies and categorized the data analysis methods by the focus of analysis and the level of analysis. The hazard-focused approach, in which the data matrix of interest is hazard × attribute, focuses on understanding how a hazard is perceived differently from the others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above studies underscore that one's perception, in this case, risk perception is a result of complex and subjective psychological and mental processes; therefore, the study of risk perception truly requires collaboration across various disciplines. Willis et al (2005) systematically studied the methodological issues in psychometric studies and categorized the data analysis methods by the focus of analysis and the level of analysis. The hazard-focused approach, in which the data matrix of interest is hazard × attribute, focuses on understanding how a hazard is perceived differently from the others.…”
Section: Introductionmentioning
confidence: 99%
“…In some instances, studies have shown the classic psychometric factor space diagram of "dread" and "unknown" is mostly valid at the individual level and argued that the conventional aggregate-level approach can still provide useful information (Kraus and Slovic 1988;Marris et al 1997). As an alternative, Willis et al (2005) have proposed an approach that provides a fine balance between aggregate-and disaggregate-level analysis. The authors presented a hybrid analysis that uses the aggregate-level factor scores to predict individuals' riskiness judgments.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of aggregating data to the job concentration level, disaggregate approach was used where the U.S. Census blocks represented the unit of analysis. Aggregated data mask variation among individual places; further, use of such data was criticized because of the inflation of the explanatory power of an analysis [56]. Accordingly, for this analysis, we used only those 1620 U.S. Census blocks which were part of the 64 identified employment concentrations (employment cluster, subcenter, or center).…”
Section: Modeling Employment Locationmentioning
confidence: 99%
“…The determination to use this combination of methodologies is based on a series of studies that show: 1) surveys and questionnaires can quantify people's attitudes towards water allocation (Syme and Nancarrow, 1996); 2) informal elicitation techniques have similar results when compared with hardcopy surveys and improved participation (Willis et. al, 2005); and 3) non-market valuation may be more effective when completed as an open-ended elicitation (Satterfield, 2001;Satterfield et al, 2000 ) .…”
Section: Pre-modeling Interview Sessions (Step1)mentioning
confidence: 99%